Pengaruh Pelaksanaan Shalat Dhuha Berbantuan Sistem Kartu Terhadap Kejujuran Dan Kedisiplinan Peserta Didik Kelas VIII Di MTsN 10 Agam - Gusmita Dewi; Salmi Wati (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2024)
Abstract. MTsN 10 Agam began to carry out Duha prayers with the help of a card system due to a decrease in the character of the students. This decline in character has worsened after the Covid-19 outbreak. Therefore it is necessary to carry out activities that will shape character in every learning activity, especially in honesty and discipline. This study aims to reveal the effect of dhuha prayer assisted by a card system on the honesty and discipline of students. This study uses quantitative data through a correlational approach, where the data in this study were obtained through a questionnaire. In presenting the data, this study uses descriptive and inferential methods. The results of this study indicate several things that answer the research hypothesis. First, there is an effect of the implementation of Duha prayer assisted by a card system on the honesty of students, as evidenced by the significance value below the value of 0.05. Second, there is an influence of the implementation of Duha prayer assisted by a card system on student discipline, as evidenced by the significance value below the value of 0.05. Third, there is an influence of the implementation of Duha prayer assisted by a card system on the honesty and discipline of students, as evidenced by the significance value below the value of 0.05. Thus it can be concluded that the implementation of Duha prayer assisted by a card system has a positive influence on the character of honesty and discipline of students.